ANALISIS UNJUK KERJA MESIN DIESEL DENGAN BAHAN BAKAR CAMPURAN PERTADEX DAN BIODIESEL DARI BIJI KEMIRI - Moh. Wafir; Digdo Listyadi; Rahma Rei Sakura (ROTOR, 2019)
The decline in fuel oil production has led to the development of alternative fuels that are renewable and more environmentally friendly. An alternative fuel that can be developed is biodiesel. In this study aims to develop alternative biodiesel fuels as a substitute for fossil oil fuels that are feasible applied to diesel engines. This study conducted a diesel engine performance test using mixed fuel from pertadex and biodiesel Aleurites Moluccana with a variation of biodiesel mixture B10, B20, and B30. From the test results using a mixture of biodiesel, the ef ective power and torque produced by the engine decreases compared to using pure pertadex. Among the three variations of the biodiesel mixture, the best ef ective power produced by B10 fuel is 277 Watt and the best torque produced by B10 fuel is 1,238 Nm. Specific fuel consumption in all biodiesel blends is increased compared to pure pertadex. Among the three variations of the biodiesel mixture, the best specific fuel consumption produced by B30 fuel is 1197,67 g/kWh. The thermal ef iciency in all biodiesel blends is increased compared to pure pertadex in B20 and B30 blends. Among the three variations of the biodiesel mixture, the best thermal ef iciency produced by B20 fuel is 7,883 %. The opacity of the engine exhaust gas produced in all biodiesel mixes is getting better compared to using pure pertadex. The best opacity of the engine exhaust gas produced in the use of B30 fuel is 2,3% HSU. Keywords: Biodiesel, Aleurites Moluccana, Diesel Engine Performance, Opacity